HYDROGEN'S ROLE IN GREEN ECONOMY: OPPORTUNITIES AND CHALLENGES IN SELECTED EUROPEAN COUNTRIES - Maria Bartekova; Sabina Janikovicova (Agora International Journal of Economical Sciences)
Hydrogen is an important element in the transition to a green economy, with its potential to play a key role in the decarbonization of industry and transport within the European Union. The aim of this article is to analyse the differences in hydrogen production and consumption between selected European countries in the context of their economic maturity. Based on data from 2020 to 2023, a quantitative analysis was conducted including variables such as hydrogen production and consumption capacity and GDP per capita. Using non-parametric tests (Kruskal-Wallis, Dwass-Steel-Critchlow-Fligner), statistically significant differences were identified between groups of countries with high and low levels of hydrogen infrastructure development. The results confirm that higher economic performance of countries is closely related to a more developed hydrogen economy. The discussion highlights the importance of investments, regulatory frameworks and technological innovations in the implementation of hydrogen solutions. The article also identifies the challenges faced by less developed countries and recommends an approach based on support and cooperation within the EU.